1989
DOI: 10.1111/j.2042-7158.1989.tb06535.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varying extents of Fluosol-DA or normal saline haemodilution on the dose dependent kinetics of phenytoin in the rat

Abstract: Phenytoin kinetics were determined in rats in which the blood was moderately haemodiluted with 20 or 40 mL kg-1 of Fluosol-DA or normal saline. Rats received one of three intravenous phenytoin doses (10, 40, 50 mg kg-1) 0.5, 24, 48, or 72 h after haemodilution and were compared with non-exchanged controls. Haemodilution with either 20 or 40 mL kg-1 of Fluosol or saline had no influence on the dose-dependent kinetics of phenytoin. Haemodilution with 40 mL kg-1 of Fluosol decreased the half-life of phenytoin's m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…PFC emulsions have the potential to alter the pharmacokinetics of drugs that may be administered simultaneously (Ravis et a1 1991). Short-term pharmacokinetic studies in rodents have demonstrated alterations in metabolic clearance and volume of distribution (Shrewsbury 1986;Shrewsbury et al 1986Shrewsbury et al , 1987aShrewsbury et al , 1989. For antipyrine (Shrewsbury et al 1986), indocyanine green (Shrewsbury et al 1987a), and phenytoin (Shrewsbury et a1 1989), clearance decreased at 24 h whereas ampicillin (Shrewsbury 1986) and propranolol (Shrewsbury et al 1987a) showed no alterations in clearance over the same periods.…”
mentioning
confidence: 99%
“…PFC emulsions have the potential to alter the pharmacokinetics of drugs that may be administered simultaneously (Ravis et a1 1991). Short-term pharmacokinetic studies in rodents have demonstrated alterations in metabolic clearance and volume of distribution (Shrewsbury 1986;Shrewsbury et al 1986Shrewsbury et al , 1987aShrewsbury et al , 1989. For antipyrine (Shrewsbury et al 1986), indocyanine green (Shrewsbury et al 1987a), and phenytoin (Shrewsbury et a1 1989), clearance decreased at 24 h whereas ampicillin (Shrewsbury 1986) and propranolol (Shrewsbury et al 1987a) showed no alterations in clearance over the same periods.…”
mentioning
confidence: 99%
“…b;Shrewsbury & White 1989a. 1990aHoke 1989) and haemodilution volumedependent (Hodges et al 1983Matsumoto-Kikuchi et al 1983;Kemner et al 1984;Shrewsbury et al 1989;Shrewsbury & White 1990b) manner after haemodilution with Fluosol-DA (Fluosol) or other blood substitutes. In each of those reports, a monoexponential equation was fitted to the plasma or blood concentration vs time data, and the Vd was calculated as the dose divided by the theoretical concentration at time zero (i.e.…”
mentioning
confidence: 99%